Hopf-pitchfork bifurcation of coupled van der Pol oscillator with delay - Cai, Yuting; Zhang, Chunrui (Nonlinear Analysis: Modelling and Control, 2017)
In this paper, the Hopf-pitchfork bifurcation of coupled van der Pol with delay is studied. The interaction coefficient and time delay are taken as two bifurcation parameters. Firstly, the normal form is gotten by performing a center manifold reduction and using the normal form theory developed by Faria and Magalhães. Secondly, bifurcation diagrams and phase portraits are given through analyzing the unfolding structure. Finally, numerical simulations are used to support theoretical analysis.
Keywords: delay; Hopf-pitchfork bifurcation; stability; coupled van der Pol model; normal form